Tropical Soda Apple: A Noxious Weed in Florida - J. Jeffrey Mullahey; Jason Ferrell; Brent Sellers (EDIS)
Revised! SS-AGR-77, a 4-page illustrated fact sheet by J. Jeffrey Mullahey, Jason Ferrell, and Brent Sellers, provides general information about this noxious weed, including description, biology, ecology, control, and precautions for shipping cattle. This version includes updated herbicide recommendations and a list of resources for further information. Published by the UF Department of Agronomy, August 2006.